Single Stage Reconstruction of ACL, PCL and Posterolateral Corner Reconstruction in Multiligamentous Knee Injury - Asif Nawaz, Wasim Anwar, Aamir Kamran, Haroon Ahmed Khan, Zeeshan Aziz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Posterolateral corner (PLC) injury leads to significant knee instability, particularly in the presence of both anterior and posterior cruciate ligament injuries comprise significant portion of knee ligamentous injuries and debates continue to reconstruct only one ligament at a time or single staged combined reconstruction. Objective: The purpose of this article is to determine short to mid-term functional outcome of single stage reconstruction of ACL,PCL and Posterolateral Corner reconstruction in multiligamentous knee injury. Methodology: This descriptive case series was conducted in department of Orthopedic, Medical teaching Institute Hayatabad Medical Complex Peshawar, Pakistanfrom Jan 2019 to June 2022. Ethical approval was taken from hospital ethical committee. 15 (KDIII L) patients of multiligament knee injuries of both cruciate ligaments and posterolateral corner injuries were included in the study. All others (KD1, KDII, KDIII M, KD IV) multiligament knee injuries were excluded. 12 cases were referred from other facilities after initial reduction and management. Two cases primarily presented to our trauma unit, urgent joint reduction was performed under general anesthesia and neurovascular status was assessed before and after reduction. Functional outcome determined in terms of Lysholm scoring system and the international Knee Documentation committee (IKDC). Patients were graded according to eight different variables: limping, weight bearing, stair climbing, squatting, instability, pain, swelling, and locking. Maximum score was 100. Scores below 68 was considered poor, from 68 to 77 was considered fair, from 77 to 90 was considered good, and above 90 considered excellent. Physical activity level was assessed by Tegner Activity Scale. Data were entered and analyzed with statistical analysis program (IBM-SPSS 23). Frequency and percentages were computed for qualitative variables like gender, type of knee injuries. Mean ±SD presented for quantitative variables. p≤0.05 were considered statistically significant. Results: 10 (66.67%) patients reported excellent outcome, 3(20%) patients have good outcome while 1 (6.67%) have fair and 1 patient (6.67 %%) reported poor results respectively on IKDC scoring system. Tengner activity level was 5.4 (range, 2 -7) 13.33% patients were level 7 activity, 40% patients were level 6 activity,33.3% patients were having level 5 score, 6.6% were level 4 activity and 6.6% were level 2 activity. The average Lysholm score was 88.3% range from (66 to 96). 13.3 % patients were having Exceptional, 66.6% patients were acceptable and 20 % patients were Fair. Conclusion: Multiligaments knee injuries are complex injuries with diverse injury pattern and clinical presentations and challenging job for sports surgeon to treat these injuries. Single stage combined reconstruction of ACL and PCL with posterolateral corner injuries with immediate postoperative rehabilitation have excellent functional outcome with low complication rate and should be followed in clinical practice. Keywords: Single stage reconstruction; ACL, PCL; Posterolateral Corner reconstruction; multiligamentous knee injury